Avaliação neuropsicológica no diagnóstico diferencial das demências infecto parasitárias e degenerativas - Soares, Vânia Lúcia Dias (2010)
Neuropsychological assessment and differential diagnosis between infective and degenerative dementias.. There are no studies comparing the neuropsychological profile of patients with parasitic infectious dementia (DIP) and other forms of primarily degenerative dementia. The objectives were to compare the neuropsychological deficits present in three groups of patients with dementia and a normal control group in relation to the DIP group. For this purpose, we prospectively evaluated 130 individuals with dementia from Dementia Unit, Hospital das Clinicas, Federal University of Goias and from the Tropical Diseases Hospital, Goiânia, aged above 18 years, divided in the following groups: infectious dementia (DIP), Alzheimer's disease (AD) , frontotemporal lobar degeneration(DLFT) , parkinsonism plus (PP) and normal controls. All underwent extensive neuropsychological assessment, addressing all cognitive domains (verbal and visual memory, attention, executive functions, gnosis, praxis, visuospatial skills, language). The productions were transcribed into tables and quantified by specific tests (Stroop, Trail Making A / B, Cancelation Test, Maze, Digit Span, Rey Figure, RAVLT, Logical Memory, Verbal Fluency, Hooper and Proverbs from WAIS). The DIP group generally presented with severe neuropsychological deficits present in multiple cognitive domains, and possibly even higher than those presented by primarily degenerative dementia in the elderly. These cognitive deficits can signal that the functional and / or lesional disturbances in DIP group undertake extensive brain areas or even that are impaired basic neuropsychological functions (attention, executive functions) that support the other functions with which are interdependent (memory, visuospatial functions). The DIP group had a higher run time, and committed more errors in the bell cancellation test than the control group (p <0.001), indicating deficits in selectivity and planning suggestive of involvement of fronto-subcortical areas. Overall, the DIP group had a performance in memory tasks higher than the AD group, equal to the DLFT group and lower than the PP group, suggesting the presence of heterogeneous hippocampal pathology in DIP group. The results emphasize that the neuropsychological assessments aid in the differential diagnosis of dementia and the topographic location of lesions associated with the predominant profile of cognitive dysfunction.